ระบบการระบายอากาศ และวัณโรคในบุคลากรทางการแพทย์ในโรงพยาบาลจุฬาลงกรณ์ - พวงเพชร วุฒิคุณาภรณ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2004)
The purposes of this cross-sectional descriptive study were to examine the quality of ventilation system and its association with tuberculosis risk among healthcare workers at Chulalongkorn Memorial Hospital. The study samples were 118 rooms in 45 wards/subdivisions with varying degrees of nosocomial TB risk in the hospital. Data were collected by interview questionnaire, walk-through survey and environmental measurements (ventilation, temperature and relative humidity) between December 2004 and Febuary 2005. Results show that the ventilation systems were mainly the split system air-conditioning(27/45 or 60.0 percent of wards and 73/118 or 61.9 percent of rooms). Only 6/45 or 13.3 percent of wards and 11/118 or 9.3 percent of rooms had adequate ventilation rates (according to the Engineering Institute of Thailand under H.M. the Kings Patronage and American Society of Heating Refrigerating and Air-Conditioning Engineers (ASHRAE) Standards). In 2004, the study revealed that there were no TB patient in two wards (no TB risk ward), while seven and eight wards admitted 1 to 5 case/year (lower risk wards) and more than 6 case/year (medium/high TB risk wards) respectively. During 1998-2002, twenty five healthcare workers had tuberculosis, they were in 14/45 wards/subdivision. However, the study showed no relationship between the quality of the ventilation system, the annual number of admitted TB patients, and the occupational TB risk for the ward/subdivision as measured by the presence of HCWs with TB. In conclusion, this study provides some information for using in the nosocomial TB risk assessment in Chulalongkorn Memorial Hospital.